PENGARUH PEMBERIAN ASI EKSLUSIF TERHADAP SIKLUS MENSTRUASI PADA IBU MENYUSUI DI KELURAHAN BATANGKALUKU - Matilda Martha Paseno (Jurnal Keperawatan Florence Nightingale, 2019)
Menstruation or menstruation is a physiological change in a woman's body that occurs periodically and is influenced by reproductive hormones. The regularity of the menstrual cycle in breastfeeding mothers is highly dependent on breastfeeding. Continuous breastfeeding can ensure the continuity of the secretion of prolactin, which is the antagonist hormone for ovulation. This study aimed to determine the effect of exclusive breastfeeding on the menstrual cycle in breastfeeding mothers in the Batakuku sub - district. The type of the study was an observational analytic with approach of cross sectional study. Sampling method using a Purposive Sampling technique with the number of samples of 12 respondents. Data were collected through questionnaires and interviews. Based on statistical test Chi-Square with Fisher Exact Test obtained value ? = 0.455> ? 0.05 then Ho received and Ha rejected, thus it can be concluded that there was no effect of exclusive breastfeeding on menstrual cycles in breastfeeding mothers in Batakuku subdistrict. Upon this conclusion, it is suggested to the next researcher candidate to be more thorough again in researching so as to get more accurate results.